Exploring young people's emotional well-being and resilience in educational contexts: A resilient space?. (May 2020) - Cocking, Chris; Sherriff, Nigel; Aranda, Kay; Zeeman, Laetitia
The term 'resilience' is pervasive in narratives of young people's emotional well-being. However, the meaning it has for those it describes is perhaps less well understood. Resilience was investigated as part of an engagement exercise into health improvement commissioning in educational contexts in the South East of England. One hundred and nine young people in total were involved, and this article reports data collected from two areas that were explored, comprising a sub-set of 58 participants: emotional well-being and resilience (n = 23) and the whole school approach (n = 35). It was apparent that while not all participants engaged with the term 'resilience' itself, they nevertheless often adopted creative individual and collective strategies to protect and enhance their emotional well-being. Furthermore, participants reported a sense of resilience that arose from a shared sense of adversity that helped strengthen collective support and solidarity, thus supporting previous work on emergent collective resilience. Theoretical and practical implications are discussed, along with a recommendation for more participatory research, so that young people can be more confident that their views are being considered within such exercises.